Referential vs. Non-referential World-Language Relations: How Do They Modulate Language Comprehension in 4 to 5-Year-Olds, Younger, and Older Adults? - Maquate, Katja; Knoeferle, Pia (Frontiers in Psychology, 2021)
Age has been shown to influence language comprehension, with delays, for in stance, in older adults’ expectations about upcoming information. We examined to what extent expectations about upcoming event information (who-does-what- to-whom) change across the lifespan (in 4-5-year old children, younger, and older adults) and as a function of different world-language relations. In a visual-world paradigm, participants in all three age groups inspected a speaker whose facial expression was either smiling or sad. Next they inspected two clipart agents (e.g., a smiling cat and a grumpy rat) depicted as acting upon a patient (e.g., a ladybug tickled by the cat and arrested by the rat). Control scenes featured the same three characters without the action depictions. While inspecting the depictions, comprehenders listened to a German sentence (e.g., "Den Marienkäfer kitzelt vergnügt der Kater"; literally: ‘The ladybug (object/patient) tickles happily the cat (subject/agent)’). Referential verb-action relations (i.e., when the actions were present) could, in principle, cue the cat-agent and so could non-referential relations via links from the speaker’s smile to ‘happily’ and the cat’s smile. We examined variation in participants’ visual anticipation of the agent (the cat) before it was mentioned depending on (a) participant age and (b) whether the referentially-mediated action depiction or the non-referentially-associated speaker smile cued the agent. The action depictions rapidly boosted participants’ visual anticipation of the agent, facilitating thematic role assignment in all age groups. By contrast, effects of the non-referentially-cued speaker smile emerged in the younger adults only. We outline implications of these findings for processing accounts of the temporally-coordinated interplay between listeners’ age-dependent language comprehension, their interrogation of the visual context, and visual context influences